No time to rest: seasonal dynamics of non-structural carbohydrates in twigs of three Mediterranean tree species suggest year-round activity - Anna M. Davidson (Nature Portfolio, 2021)
Abstract Perennial plants in temperate climates evolved short and long-term strategies to store and manage reserves in the form of non-structural carbohydrates (NSC; soluble sugars (SC) and starch (St)). NSC storage allows plants to survive seasonal periods of photosynthetic inactivity (dormancy). To study year-to-year seasonal patterns of trees’ NSC dynamics that control phenology and yields, we established a large scale, multi-year study called the “Carbohydrate Observatory” using a citizen science approach with ~ 590 sites throughout the Central Valley of California. Monthly sampling tracked seasonal trends of starch and sugar levels in both xylem and phloem of twigs in Prunus dulcis, Pistacia vera and Juglans regia. Presented is the initial technical analysis of the first 3 years. With no exception, levels of reserves changed continuously throughout the year suggesting that even during dormancy, the average concentration of NSC, starch and sugars varies seasonally. In general, carbohydrate reserves are highest entering dormancy. During winter, NSCs slowly decrease to depletion during bloom time and remain low during summer until recovery near harvest. Starch is the major reserve compound in the wood of P. dulcis and P. vera while soluble sugars are the major reserves in J. regia. NSC content fluctuates throughout a season and significantly varies between years suggesting intrinsic and climatic effects on trees’ energy reserves.